A low temperature resistant hydrogel solid electrolyte and its preparation method and application
By blending sodium alginate and glycerol at a specific temperature to form a gel and soaking in an inorganic salt solution, the problem of complex preparation of existing gel electrolytes and easy to freeze at low temperatures is solved, and hydrogel solid electrolyte with high freezing resistance and high ionic conductivity is prepared, which is suitable for battery applications.
Patent Information
- Application Number
- CN202210623554.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-06-02
AI Technical Summary
The existing ionically conductive gel electrolytes are complex in preparation and are prone to freeze under low temperature conditions, resulting in deterioration of battery electrochemical performance.
By mixing sodium alginate and glycerol at specific temperatures to form a highly tough gel and soaking in an inorganic salt solution, a hydrogel solid electrolyte with high ionic conductivity and high freezing resistance was prepared.
The prepared hydrogel solid electrolyte does not freeze at -30°C for 12 hours, maintains good flexibility, and has high ionic conductivity, and is suitable for battery solid electrolytes.
Smart Images

Figure CN115058026B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery solid electrolytes, and more specifically, to a low-temperature resistant hydrogel solid electrolyte and a preparation method and application thereof. Background Art
[0002] Aqueous batteries are considered to be ideal power sources for wearable electronic devices due to their safety, environmental friendliness, and ease of manufacture. Traditional flexible aqueous batteries mostly use aqueous solutions as electrolytes, which are prone to electrolyte leakage when subjected to mechanical stresses such as bending or stretching, causing the battery to fail to work. The use of hydrogel solid electrolytes can not only solve the leakage problem caused by the electrolyte, but also integrate the functions of the diaphragm and the electrolyte, which helps to simplify the battery manufacturing process. However, at low temperatures, especially sub-zero temperatures, traditional hydrogel electrolyte materials are prone to freezing and lose flexibility and conductivity. Therefore, at sub-zero temperatures, the overall electrochemical performance of the battery declines, or even stops working, seriously affecting its energy supply and wearable applications. A common solution is to add a cryoprotectant (such as glycerol, etc.) to the hydrogel to form stronger hydrogen bonds between water molecules and cryoprotectant molecules, inhibiting the formation of ice crystals, thereby effectively lowering the freezing point of the hydrogel.
[0003] In order to alleviate the burden of electronic waste on the global environment caused by non-degradable components in flexible electronic devices, researchers are particularly interested in the application of biodegradable materials (cellulose, chitin, sodium alginate and starch, etc.) in flexible electronic devices and energy storage devices. Sodium alginate has the advantages of biodegradability, low price, abundant sources and renewable, and can be used to design and prepare multifunctional ion conductive gels. Sodium alginate-based gels usually show low toughness, high brittleness and low antifreeze properties.
[0004] The Chinese patent "Preparation and Application of Gel Electrolyte for Antifreeze Zinc-based Batteries" discloses a method for preparing an antifreeze hydrogel by uniformly mixing a sodium alginate aqueous solution with an initiator, a cross-linking agent, and a monomer for free radical polymerization, and then immersing the hydrogel in a liquid electrolyte mixed with zinc salt and lithium salt to obtain an ion-conductive gel electrolyte. However, this method requires a sodium alginate aqueous solution to undergo a free radical polymerization reaction with an initiator, a cross-linking agent, and a monomer at a certain heating temperature and time to form a gel, which is a complex process, and the antifreeze performance of the hydrogel prepared by the method still needs to be further improved.
[0005] Therefore, it is of great significance to study ion-conductive gel hydrogel solid electrolytes with simple preparation methods and high antifreeze properties. Summary of the invention
[0006] In order to solve the problem that the preparation of existing ion-conductive gel electrolytes is complicated and the antifreeze performance still needs to be further improved, the present invention mixes sodium alginate and glycerol under specific temperature conditions to form a high-toughness gel, and then soaks it in an inorganic salt solution to form a hydrogel solid electrolyte with high ionic conductivity and high antifreeze performance, and applies it to batteries. The preparation process of the present invention is simple, and the prepared hydrogel solid electrolyte has high ionic conductivity, does not freeze at -30°C for 12 hours, and maintains good flexibility.
[0007] Another object of the present invention is to provide a low temperature resistant hydrogel solid electrolyte.
[0008] Another object of the present invention is to provide an application of the above-mentioned low-temperature resistant hydrogel solid electrolyte.
[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0010] A method for preparing a low-temperature resistant hydrogel solid electrolyte comprises the following steps:
[0011] S1. Mixing sodium alginate and glycerol, and reacting at 70-80° C. to prepare a gel;
[0012] S2. The gel obtained in S1 is immersed in an inorganic salt solution to obtain the low temperature resistant hydrogel solid electrolyte;
[0013] The mass volume ratio of sodium alginate and glycerol described in S1 is 1:(5-9) g / mL.
[0014] Sodium alginate-based gels usually exhibit low toughness, high brittleness and low antifreeze properties. Studies have found that glycerol can improve the antifreeze properties of gels, so glycerol can be added to sodium alginate-based gels as a cryoprotectant. Generally, glycerol needs to be blended with an initiator, a cross-linking agent, a monomer, and sodium alginate to form a gel so that glycerol can be successfully added to the sodium alginate-based gel. For example, directly blending sodium alginate and glycerol at room temperature cannot form a gel; directly mixing sodium alginate, glycerol and inorganic salts or inorganic salt aqueous solutions at room temperature cannot form an ion-conductive gel solid electrolyte.
[0015] After many studies, the inventor creatively discovered that when sodium alginate and glycerol are blended under specific temperature conditions, a gel with high toughness can be formed without an initiator or a cross-linking agent. In addition, the abundant and evenly distributed carboxyl and hydroxyl hydrophilic groups on the sodium alginate molecular chain in the sodium alginate / glycerol gel are conducive to the absorption and dissociation of ions, thereby promoting the migration of electrolyte ions and improving the ionic conductivity of the gel. At the same time, the hydroxyl groups of glycerol combine with water through hydrogen bonds, reducing the interaction between water molecules, preventing the formation of ice crystals, and thus improving the antifreeze performance of the gel; making the sodium alginate / glycerol gel of the present application conducive to improving ionic conductivity and having high antifreeze performance.
[0016] Then the sodium alginate / glycerol gel is immersed in an inorganic salt solution to allow metal ions to enter the sodium alginate / glycerol gel. The ionic conductivity of the antifreeze hydrogel is improved by the inorganic salt ion conduction, and a hydrogel solid electrolyte with high ionic conductivity and high antifreeze performance can be obtained. The ionic conductivity of the prepared hydrogel solid electrolyte can reach 28.80mS cm -1 , it can remain free of ice for 12 hours at -30℃ and maintains good flexibility.
[0017] Preferably, the mass volume ratio of sodium alginate and glycerol in S1 is 1:(7-9) g / mL.
[0018] More preferably, the mass volume ratio of sodium alginate and glycerol in S1 is 1.2:10 g / mL
[0019] Preferably, the reaction time at 70-80° C. in S1 is not less than 2 h.
[0020] More preferably, the time described in S1 is 2 to 3 hours.
[0021] Furthermore, the heating temperature in S1 is 80° C. and the heating time is 2 h.
[0022] Conventional inorganic salts in the art can be used in the present invention.
[0023] Preferably, the inorganic salt in the inorganic salt solution in S2 is one or more of zinc salt, manganese salt or lithium salt.
[0024] More preferably, the inorganic salt in the inorganic salt solution in S2 is one or more of ZnSO4, MnSO4, Li2SO4 or Zn(NO3)2.
[0025] Furthermore, the inorganic salt in S2 is one or more of ZnSO4, MnSO4 or Li2SO4.
[0026] Preferably, the inorganic salt concentration in the inorganic salt solution in S2 is 1-2 mol / L, and the mass volume ratio of sodium alginate to the inorganic salt solution is 1:(6-8) g / mL.
[0027] Preferably, the soaking time in S2 is 4 to 12 hours.
[0028] A low-temperature resistant hydrogel solid electrolyte is prepared by the method.
[0029] The low temperature resistant hydrogel solid electrolyte is applied to battery solid electrolyte.
[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0031] The present invention forms a gel by mixing sodium alginate and glycerol under specific temperature conditions. It does not require a sodium alginate aqueous solution to react with an initiator, a crosslinking agent, or a monomer to form a gel by free radical polymerization. The preparation method is simple and overcomes the problem that sodium alginate, glycerol, and inorganic salts cannot form a hydrogel when directly mixed. The ionic conductivity of the prepared hydrogel solid electrolyte can reach 28.80 mS cm -1 , it can remain free of ice for 12 hours at -30℃ and maintains good flexibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a picture of the sodium alginate / glycerol gel prepared in the preparation method S1 of the present application.
[0033] Figure 2 This is a state diagram of the hydrogel prepared in Example 1 at -30°C for 12 hours.
[0034] Figure 3 This is a diagram of the turbid solution formed by guar gum and glycerol in Comparative Example 3.
[0035] Figure 4 This is a rate performance test diagram of a flexible zinc ion battery using the hydrogel prepared in Example 1 as a solid electrolyte.
[0036] Figure 5 This is a test diagram of the cycle performance of a flexible zinc ion battery using the hydrogel prepared in Example 1 as a solid electrolyte. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention will be described clearly and completely below, but the implementation manner of the present invention is not limited thereto.
[0038] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0039] Example 1
[0040] This embodiment provides a method for preparing a low-temperature resistant hydrogel solid electrolyte, comprising the following steps:
[0041] S1.1.2 g of sodium alginate and 10 mL of glycerol were mixed and then heated at 80°C for 2 h to prepare a transparent sodium alginate / glycerol gel.
[0042] Figure 1 This is a picture of the prepared sodium alginate / glycerol gel. It can be seen that the gel is transparent in color and has a certain degree of flexibility.
[0043] S2. Prepare 20mL of electrolyte containing 2mol / L ZnSO4+0.1mol / L MnSO4, and immerse the gel in the electrolyte for 12h to form a sodium alginate / glycerol / ZnSO4 hydrogel solid electrolyte containing Zn ions, with an ionic conductivity of 28.80mScm -1 The hydrogel did not freeze at -30°C for 12 hours and maintained good flexibility.
[0044] Figure 2 This is a state diagram of the prepared sodium alginate / glycerol / ZnSO4 hydrogel solid electrolyte at -30℃ for 12h. It can be seen that the hydrogel still maintains a gel state and does not freeze.
[0045] Example 2
[0046] This embodiment provides a method for preparing a low-temperature resistant hydrogel solid electrolyte, comprising the following steps:
[0047] 1.2g sodium alginate and 10mL glycerol were mixed and then heated at 80℃ for 2h to prepare a transparent gel. Then 20mL of electrolyte containing 2mol / L ZnSO4 was prepared and the gel was immersed in the electrolyte for 4h to form a hydrogel solid electrolyte containing Zn ions with an ionic conductivity of 17.77mS cm -1 .
[0048] Example 3
[0049] This embodiment provides a method for preparing a low-temperature resistant hydrogel solid electrolyte, comprising the following steps:
[0050] 3g sodium alginate and 25mL glycerol were mixed and then heated at 80℃ for 2h to prepare a transparent sodium alginate / glycerol gel. 20mL of electrolyte containing 2mol / L ZnSO4+0.1mol / L MnSO4 was prepared and the gel was immersed in the electrolyte for 12h to form a sodium alginate / glycerol / ZnSO4 hydrogel solid electrolyte containing Zn ions with an ionic conductivity of 15.40mS cm -1 The hydrogel did not freeze at -30°C for 12 hours and maintained good flexibility.
[0051] Example 4
[0052] This embodiment provides a method for preparing a low-temperature resistant hydrogel solid electrolyte, comprising the following steps:
[0053] 3g sodium alginate and 15mL glycerol were mixed and then heated at 80℃ for 2h to prepare a transparent sodium alginate / glycerol gel. 20mL of electrolyte containing 2mol / L ZnSO4+0.1mol / L MnSO4 was prepared and the gel was immersed in the electrolyte for 12h to form a sodium alginate / glycerol / ZnSO4 hydrogel solid electrolyte containing Zn ions with an ionic conductivity of 17.20mS cm -1 The hydrogel did not freeze at -30°C for 12 hours and maintained good flexibility.
[0054] Example 5
[0055] This embodiment provides a method for preparing a low-temperature resistant hydrogel solid electrolyte, comprising the following steps:
[0056] 3g sodium alginate and 15mL glycerol were mixed and then heated at 70℃ for 2h to prepare a transparent sodium alginate / glycerol gel. 20mL of electrolyte containing 2mol / L ZnSO4+0.1mol / L MnSO4 was prepared and the gel was immersed in the electrolyte for 12h to form a sodium alginate / glycerol / ZnSO4 hydrogel solid electrolyte containing Zn ions with an ionic conductivity of 18.00mS cm -1 The hydrogel did not freeze at -30°C for 12 hours and maintained good flexibility.
[0057] Comparative Example 1
[0058] 1.2 g of sodium alginate and 10 mL of glycerol were mixed together and could not form a gel even if left for 5 days without heating.
[0059] Comparative Example 2
[0060] 1.2 g of sodium alginate and 10 mL of ethylene glycol were mixed and then heated at 70°C for 2 h, but no gel was formed.
[0061] Comparative Example 3
[0062] 1.2 Guar gum and 10 mL of glycerol were mixed and then heated at 80°C for 2 h, but no gel was formed.
[0063] like Figure 3 As shown, when the same amount of guar gum and glycerin are mixed and heated under the same conditions, only a turbid solution can be obtained.
[0064] As can be seen from Examples 1 to 5, the present invention forms gel by mixing sodium alginate and glycerol at a specific temperature, without the need for free radical polymerization of sodium alginate aqueous solution with initiator, crosslinker, and monomer to form gel. The preparation method is simple and overcomes the problem that sodium alginate, glycerol, and inorganic salts cannot form gel by direct mixing. The prepared gel has an ionic conductivity of >15mS cm -1The ionic conductivity of the gel prepared in Example 1 can reach 28.80 mS cm -1 , it does not freeze at -30℃ for 12h and maintains good flexibility.
[0065] Compared with the embodiments, in Comparative Example 1, sodium alginate and glycerol were not blended at a specific temperature, and gel could not be formed; in Comparative Example 2, glycerol was replaced by ethylene glycol, and in Comparative Example 3, sodium alginate was replaced by guar gum, and gel could not be formed even when blended at a specific temperature.
[0066] The performance of the battery assembled with the low-temperature resistant hydrogel solid electrolyte prepared in Example 1 was tested.
[0067] Mix 70wt.% α-MnO2 powder, 20wt.% rGO (reduced graphene oxide) and 10wt.% PVDF (polyvinylidene fluoride), add an appropriate amount of NMP (N-methyl-2-pyrrolidone) to form a slurry, and evenly coat the slurry on the carbon cloth. Dry the carbon cloth electrode coated with the slurry at 70℃ for 6h to obtain the MnO2 / rGO positive electrode.
[0068] Dissolve 2.5g ZnSO4·7H2O, 2.5g Na2SO4, and 0.4g H3BO3 in 20mL deionized water to prepare an electroplating solution. Place the desired electrodes in the electroplating solution, using carbon cloth as the working electrode and platinum foil as the counter electrode and reference electrode. -2 Under a constant current density of , the electroplated zinc negative electrode can be obtained by electroplating metal zinc for 15 minutes.
[0069] The electroplated zinc negative electrode, locust bean gum hydrogel electrolyte, and MnO2 / rGO positive electrode were stacked and assembled into a battery, and the performance was tested at different current densities.
[0070] like Figure 4 and Figure 5 As shown, the battery exhibits a high specific capacity (current density of 0.15A g -1 The specific capacity is 375 mAh g -1 ), excellent rate characteristics (current density of 6.0A g -1 The specific capacity is 105.4 mAh g -1 ) and good cycle characteristics.
[0071] The test results of the remaining embodiments are basically consistent with those of embodiment 1.
[0072] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made on the basis of the above. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a low-temperature resistant hydrogel solid electrolyte, characterized in that: The following steps are involved: S1. Mixing sodium alginate and glycerol, and reacting at 70-80° C. to prepare a gel; S2. The gel obtained in S1 is immersed in an inorganic salt solution to obtain the low temperature resistant hydrogel solid electrolyte; The mass volume ratio of sodium alginate and glycerol in S1 is 1:(5-9) g / mL; The preparation method does not require a sodium alginate aqueous solution to form a gel.
2. The preparation method according to claim 1, characterized in that: The mass volume ratio of sodium alginate and glycerol described in S1 is 1:(7-9) g / mL.
3. The preparation method according to claim 1, characterized in that: The reaction time at 70-80° C. in S1 is not less than 2 h.
4. The preparation method according to claim 3, characterized in that: The time described in S1 is 2 to 3 hours.
5. The preparation method according to claim 1, characterized in that: The inorganic salt in the inorganic salt solution in S2 is one or more of zinc salt, manganese salt or lithium salt.
6. The preparation method according to claim 5, characterized in that: The inorganic salt in the inorganic salt solution in S2 is one or more of ZnSO4, MnSO4, Li2SO4 or Zn(NO3)2.
7. The preparation method according to claim 1, characterized in that: The inorganic salt concentration in the inorganic salt solution in S2 is 1-2 mol / L, and the mass volume ratio of sodium alginate to the inorganic salt solution is 1:(6-8) g / mL.
8. The preparation method according to claim 1, characterized in that: The soaking time in S2 is 4 to 12 hours.
9. A low temperature resistant hydrogel solid electrolyte, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the low temperature resistant hydrogel solid electrolyte according to claim 9 in preparing battery solid electrolyte.
Citation Information
Patent Citations
Degradable low-temperature-resistant hydrogel electrolyte as well as preparation method and application thereof
CN113416273A
Protective gel composition for wounds
US4393048A